POLEMIK POLITIK DAN STRATEGI DAKWAH - FATHURRAHMAN FATHURRAHMAN (TASÂMUH, 2019)
This study was conducted to obtain an overview of social phenomena in the political year and the da'wah strategies needed because of the political choices needed to exchange admonitions between people. The difference is increasingly put forward, and diversity is increasingly not seen as solid. Mutual intrigue conflicts between one candidate pair with another candidate always apply. Dropping has become a political problem, but harassing, and blaspheming, even disbelief among people is conflicts caused by differences in political choices. Then da'wah was successfully crushed by using politics. The preachers no longer see da'wah as a medium of peace, agreeing that their pulpits are used as a demonstration of their political election campaigns and even messages that are delivered provocatively and corner other groups. Da'wah must be present as a mediator amid political choice conflict.